2004
DOI: 10.1063/1.1804547
|View full text |Cite
|
Sign up to set email alerts
|

Heating effect on steady and unsteady horizontal laminar flow of air past a circular cylinder

Abstract: Extensive numerical experiments were carried out to study the effect of cylinder heating on the characteristics of the flow and heat transfer in a two-dimensional horizontal laminar flow of air past a heated circular cylinder for the range of Reynolds numbers 0.001⩽Re⩽170. The fluid was treated as incompressible (density is independent of the pressure) while the variation of the fluid properties with temperature was taken into account. By including the transient density term of the continuity equation, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 34 publications
3
35
1
Order By: Relevance
“…17 is also plotted as the solid line in this figure for a comparison. Results from the non-isothermal cases 7,12,14,19,20 have revealed that the vortex-shedding frequency decreases with increasing cylinder temperature for the PVS mode. Similar trend also can be found for the vortex shedding frequency of OVS mode, i.e., the shedding frequency decreases with increasing temperature ratio.…”
Section: -3mentioning
confidence: 99%
“…17 is also plotted as the solid line in this figure for a comparison. Results from the non-isothermal cases 7,12,14,19,20 have revealed that the vortex-shedding frequency decreases with increasing cylinder temperature for the PVS mode. Similar trend also can be found for the vortex shedding frequency of OVS mode, i.e., the shedding frequency decreases with increasing temperature ratio.…”
Section: -3mentioning
confidence: 99%
“…They have shown that the unsteady drag variation was smaller compared to the steady case and the lift coefficient strongly increased with Reynolds number. (Shi et al, 2004) investigated the effect of temperature dependent viscosity and density of air on the fluid flow and heat transfer from a heated circular cylinder for the range 10 -3 ≤Re≤170. (Mahír and Altaç, 2008) has investigated the unsteady laminar convective heat transfer from isothermal circular cylinders of tandem arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…This regime continues up to about Re = 200 before making way for the onset of threedimensional flow. Also, several numerical and experimental studies have been performed to study the fluid flow and heat transfer characteristics over a circular cylinder (Chakraborty, Verma, and Chhabra, 2004;Chhabra, Soares, and Ferreira, 2004;Golani and Dhiman, 2004;Mahír and Altaç, 2008;Park, Kwon, and Choi, 1998;Posdziech and Grundmann, 2007;Shi, Gerlach, Breuer, Biswas, and Durst, 2004;Tritton, 1959).…”
Section: Introductionmentioning
confidence: 99%
“…In available studies, there are number of studies based on theoretical, experimental and numerical data on the flow and heat transfer around the circular cylinders over a wide range of Reynolds numbers, Prandtl numbers (Pr), power law fluids etc. (Chakraborty et al, 2004, Golani and Dhiman, 2004, Mahír and Altaç, 2008, Park et al, 1998, Posdziech and Grundmann, 2007, Shi et al, 2004, Tritton, 1959, Rahman et al, 2007. Golani and Dhiman (2004) has studied Fluid flow and heat transfer across a circular cylinder in the unsteady flow regime for Re 50 to 180 at Pr=0.7 by using CFD commercial software FLUENT.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that the unsteady drag variation was smaller compared to the steady case and the lift coefficient strongly increased with Reynolds number. Shi et al (2004) investigated the effect of temperature dependent viscosity and density of air on the fluid flow and heat transfer from a heated cylinder for the range. It is observed that thermal conductivity of nanofluid is higher than that of the base fluids when the nanoparticles are mixed with a small amount (Eastman et al, 2001, Xuan andLi, 2000).…”
Section: Introductionmentioning
confidence: 99%